Microclimate evaluation of strap-based wheelchair seating systems for persons with spinal cord injury: A pilot study. Issue 3 (August 2018) - Olney, Christine M.; Simone, Amanda; Hanowski, Kristin; Rector, Thomas S.; Goldish, Gary D.; Hansen, Andrew H.; Ferguson, John E.
Abstract: Study purpose: The purpose of this pilot study was to assess microclimate characteristics of two versions of a strap-based wheelchair seating system (perforated and solid straps) and to conduct preliminary microclimate comparisons of subjects' current wheelchair seating systems. Materials and methods: In this pilot study, the microclimate properties of two variations (solid and perforated) of a strap-based seating system were compared with two commonly used seating systems. Six subjects sat on three different seating systems each for 100-min test periods, while temperature and relative humidity were measured with a single sensor adjacent to the skin-seat interface. Additionally, thermal images of the seat interface were collected before and after each test period. Results: The thermal images revealed that the maximum surface temperature of the solid-strap-based seating system was significantly lower than the other seating systems, −1.21 °C. (95% CI -2.11 to −0.30, p = 0.02), immediately following transfer out of the seat. Five minutes after transferring out of the seat, the perforated-strap seat was significantly cooler than the other seats −0.94 °C. (95% CI -1.59 to −0.30), p = 0.01, as was the solid-strap-based seat, −1.66 °C. (95% CI -2.69 to −0.63), p = 0.01. There were no significant differences in interface temperature or relative humidity measured with the single sensor near the skin-seat interface. Conclusion: This pilot study offers preliminary evidence regarding the microclimate of the strap-based seating systems compared with other common seating systems. Clinically, the strap-based seating system may offer another option for those who struggle with microclimate management. Highlights: Thermal imagery depicts differences in cooling among different seating systems. Strap-based seating cools faster. Clinically the strap-based seating may offer faster cooling during a forward lean pressure relief.